FUNCTION, FORM, AND MEANING OF RITUAL AND MARKET IN HISTORICAL SITE OF KAMPUNG LUAR BATANG, JAKARTA, INDONESIA - Ashadi; Anisa; RatnaDewi (International Journal of Research -GRANTHAALAYAH, 2017)
Functions or activities that occur on a historic site did by a community will affect the formation of its physical environment. This research observes the ritual and market activities did by the community in the historic site of KampungLuarBatang, North Jakarta, and sees its influence on the formation of its physical environment. The purpose of this research is to explore the meaning of ritual and market in historic site of KampungLuarBatang, by relating the function or activity of ritual and market with the formation of its physical environment. The research method used is descriptive qualitative interpretative method. The observed function or activity is a pilgrimage ritual activity in the historic mosque building and market activity around the mosque. The form of physical environment observed is the spaces used as places of pilgrimage and market. The conclusion of this research is the function or activity of pilgrimage ritual and market did by the community of KampungLuarBatang, North Jakarta, has a meaning of survival strategy in the modern city environment of Jakarta.